2000
DOI: 10.1086/467468
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mandatory Disclosure Laws on Product Choices: An Analysis of the Salad Dressing Market

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. AbstractThe Nutrition Labeling and Education Act (NLEA) requires most food products to include a nutrition label. Prior to the NLEA, labeling was voluntary. This study uses nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
149
2
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(159 citation statements)
references
References 0 publications
3
149
2
5
Order By: Relevance
“…The widespread use of these labels might be an indication that they are perceived as a successful tool of altering consumer behavior, however, availability of information does not necessarily ensure that it will be incorporated into consumer behavior (e.g. Mathios 2000, Ippolito and Pappalardo 2002, Jin and Leslie 2003, Teisl, Bockstael and Levy 2001, Ippolito and Mathios 1995. This research provides an ex post cost benefit analysis of changes in labeling regulations under the National Organic Program (NOP), essential for an evaluation of this program.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widespread use of these labels might be an indication that they are perceived as a successful tool of altering consumer behavior, however, availability of information does not necessarily ensure that it will be incorporated into consumer behavior (e.g. Mathios 2000, Ippolito and Pappalardo 2002, Jin and Leslie 2003, Teisl, Bockstael and Levy 2001, Ippolito and Mathios 1995. This research provides an ex post cost benefit analysis of changes in labeling regulations under the National Organic Program (NOP), essential for an evaluation of this program.…”
Section: Introductionmentioning
confidence: 99%
“…Previous empirical studies of the effects of voluntary and/or of mandatory product labeling in the food sector have tended to focus on the provision of nutritional information and exhibit mixed results regarding effectiveness of information provision (see, for example Ippolito and Mathios, 1990, Mojduszka and Caswell, 2000, Ippolito and Mathios, 1995, Mathios, 2000, Teisl, Bockstael, and Levy, 2001. Evaluating ecolabels, Teisl, Roe, and Hicks (2002) report that dolphin-safe labels resulted in changes in aggregate tuna consumption, and Jin and Leslie (2003) conclude that consumer demand is sensitive to mandatory and voluntary display of hygiene quality grade cards in the Los Angeles restaurant market.…”
Section: Introductionmentioning
confidence: 99%
“…Possible enhanced outreach methods include health-advertising campaigns (on public transportation, for example), in-store advisory signs, and mandatory product labeling. Mathios (2000) showed that labeling induces important consumption responses, and Teisl et al (2002) showed that point of consumption labeling is particularly effective for canned fish. 29…”
Section: Discussionmentioning
confidence: 99%
“…Многие потребители знакомы с такими широко распространенными правилами раскрытия информа-ции в сфере торговли, как требование указания цены 61 , информации о питательных веществах 62 , правдивости рекламы 63 . Требования в отдельных отраслях менее известны.…”
Section: товары и услугиunclassified
“…также [10] (обоснование, что Berghuis «считает [правило Миранды] необязательным требованием раскрытия ин-формации, а не методом защиты от принудительного допроса»). 61 . Многие требования раскрытия информации от-носятся к сделкам с автомобилями.…”
Section: товары и услугиunclassified